Hubungan Antara CT Value pada Test RT-PCR Terhadap Parameter Klinis Pasien COVID-19 - Josi Jeremia Manurung; Asep Sukohar (Medula, 2021)
Detection of SARS-CoV-2 by reverse transcription-PCR (RT-PCR) test on nasopharyngeal swab specimens is the main diagnostic method for COVID-19, usually reported qualitatively as positive or negative using a defined cut-off, either based on the CT value. or integrated with an automated algorithm that interprets different parameters of the potential amplification. The CT value was inversely related to the number of viruses in the sample. Consequently, the CT value could indirectly indicate the level of viral replication activity, which affects SAR-CoV-2 infectivity in patients, but this does not differentiate between infectious and non-infectious viruses. Several studies stated that there was no correlation between CT values and severity, in the pneumonia and non-pneumonia groups, symptomatic and asymptomatic patients, the presence or absence of olfactory or tasting dysfunction, as well as on leukocytes, neutrophils, lymphocytes, platelets and C-reactive protein. Many factors that influence the CT value such as the timing of sample collection, method of collection of the sample, the kit used, and the skills of the health worker are biased which can affect the CT value. Further research is needed on the correlation of CT values in COVID-19 patients.